The Central America Universities at the International Rankings - Buitrago Reyes, Lesbia Jeannette (Revista General de Información y Documentación, 2022)
Research in Higher Education institutions is one of the three fundamental pillars of universities, along with teaching and links to society; being the latter the one that identifies the concrete problems, the research tries to solve them and both enrich the chair. The objective of this article is to analyze the research position of Central American universities and suggest strategies to influence the indicators of two internationally prestigious classifiers: SCImago Institutions Ranking (SIR) and Ranking Quacquarelli Symonds® (QS), which include indicators in their methodology research. The quantitative approach was used. Thirteen strategies are presented with their respective lines of action and the impact on their indicators so that universities can establish their own strategies according to these results. World SIR ranked the University of Universidad de Costa Rica (UCR), Universidad Nacional de Costa Rica (UNA), Instituto Tecnológico de Costa Rica (TEC) and Universidad Tecnológica de Panamá (UTP). In QS Mundial classified the UCR, TEC, Universidad Latinoamericana de Ciencia y Tecnología (ULACIT), UNA, Universidad Tecnológica de Panamá (UTP), Universidad de Panamá (UP) and Universidad Nacional Autónoma de Honduras (UNAH). It is sought not only for Central American universities to improve their position in these international rankings, but also to contribute to the progress of the societies where they are registered.